Metabolomic Profiling in Acute ST‐Segment–Elevation Myocardial Infarction Identifies Succinate as an Early Marker of Human Ischemia–Reperfusion Injury. Issue 8 (6th April 2018) - Kohlhauer, Matthias; Dawkins, Sam; Costa, Ana S. H.; Lee, Regent; Young, Timothy; Pell, Victoria R.; Choudhury, Robin P.; Banning, Adrian P.; Kharbanda, Rajesh K.; ,; Saeb‐Parsy, Kourosh; Murphy, Michael P.; et al.
Abstract : Background: Ischemia–reperfusion injury following ST‐segment–elevation myocardial infarction (STEMI) is a leading determinant of clinical outcome. In experimental models of myocardial ischemia, succinate accumulation leading to mitochondrial dysfunction is a major cause of ischemia–reperfusion injury; however, the potential importance and specificity of myocardial succinate accumulation in human STEMI is unknown. We sought to identify the metabolites released from the heart in patients undergoing primary percutaneous coronary intervention for emergency treatment of STEMI. Methods and Results: Blood samples were obtained from the coronary artery, coronary sinus, and peripheral vein in patients undergoing primary percutaneous coronary intervention for acute STEMI and in control patients undergoing nonemergency coronary angiography or percutaneous coronary intervention for stable angina or non‐STEMI. Plasma metabolites were analyzed by targeted liquid chromatography and mass spectrometry. Metabolite levels for coronary artery, coronary sinus, and peripheral vein were compared to derive cardiac and systemic release ratios. In STEMI patients, cardiac magnetic resonance imaging was performed 2 days and 6 months after primary percutaneous coronary intervention to quantify acute myocardial edema and final infarct size, respectively. In total, 115 patients undergoing acute STEMI and 26 control patients were included. Succinate was the only metabolite significantly increased in coronary sinus blood compared with venous blood in STEMI patients, indicating cardiac release of succinate. STEMI patients had higher succinate concentrations in arterial, coronary sinus, and peripheral venous blood than patients with non‐STEMI or stable angina. Furthermore, cardiac succinate release in STEMI correlated with the extent of acute myocardial injury, quantified by cardiac magnetic resonance imaging. Conclusion: Succinate release by the myocardium correlates with the extent of ischemia.